(untitled) (Research, Society and Development, 2022)
Objective: to evaluate the effect of auriculotherapy on cortisol levels in Primary Health Care nurses with Burnout Syndrome. Method: a quasi-experimental study with a pre-test/post-test design, with 75 nurses from Primary Health Care, carried out between January and June 2018. The analysis compared the slopes of the mean salivary cortisol concentration curves of nurses who had different stages of Burnout. Results: normal circadian pattern was evidenced with high cortisol levels in the morning and lower levels at night. Comparing the hormone concentration before and after auriculotherapy, a significant reduction was observed in nurses classified as having high stages of Burnout. Conclusion: there was no significant association between hormone concentration and Burnout, however, physical and mental clinical improvement was reported by nurses, reducing hormone concentration in cases with high levels of the syndrome.